A Multi-Criteria Model for Assessing Photovoltaic Panels - Dorota GAWRONSKA (Communications of International Proceedings, 2021)
This article presents the proposed multi-criteria model for assessing variants of photovoltaic panels based on criteria defined by general parameters (e.g., price), technical parameters of the panels, and the PVEL laboratory test results. Based on the adopted criteria, a hierarchical structure was created. Using multi-criteria programming, an algorithm for evaluating photovoltaic panels was presented, which enables the determination of the optimal variant of photovoltaic panels, considering the importance of individual criteria.
Keywords: Multi-criteria programming; photovoltaic panels; technical parameters of photovoltaic panels.